Ceftolozane-tazobactam for the Treatment of Multi Drug-resistant Pseudomonas aeruginosa (MDRPA) Infections. (4th October 2017) - Molnar, Esther; Heil, Emily; Claeys, Kimberly; Hiles, Jon; Gallagher, Jason
Abstract: Background: Ceftolozane-tazobactam (TOL-TAZ) is a novel cephalosporin/β-lactamase inhibitor combination with potent activity against Pseudomonas aeruginosa, including MDRPA. TOL-TAZ use for MDRPA infections has not been well-studied. Methods: We conducted a retrospective study to describe outcomes of patients treated with TOL-TAZ for MDR Pseudomonas aeruginosa infections at 3 academic medical centers. Patients were age ≥ 18 years who had MDRPA isolated in culture and received TOL-TAZ for at least 24 hours. The primary outcomes were 30-day and in-hospital mortality. Secondary outcomes were microbiological cure and clinical success. Microbiological cure was defined as negative culture at end of therapy; cure was presumed when clinical success occurred without follow-up cultures. Clinical success was defined as resolution of all signs and symptoms of infection. TOL-TAZ susceptibility results were collected when available. Results: Conclusion: In this severely ill population with MDRPA infections, 79.4% and 76.5% of patients were alive at 30-days and at the end of their stay, respectively. Some patients had positive cultures despite clinical resolution. TOL-TAZ is a potential option for patients with MDRPA infections. Disclosures: E. Molnar, Merck: Grant Investigator, Research grant. J. Gallagher, Merck: Consultant, Grant Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee, Educational grant and Speaker honorarium. Allergan: Scientific Advisor and Speaker's Bureau, Consulting fee and Speaker honorarium. Astellas: Scientific Advisor and Speaker's Bureau, Consulting fee and Speaker honorarium. Achaogen: Scientific Advisor, Consulting fee. Cidara: Consultant, Consulting fee. Theravance: Scientific Advisor, Consulting fee. Paratek: Scientific Advisor, Consulting fee. The Medicines Company: Scientific Advisor, Consulting fee.